The Concept, Nature and Manifestations of Terrorism - Almatov Sanjar Zakirjonovich (International Journal on Integrated Education, 2022)
In this article, the concept, nature and manifestations of terrorism are opened with scientific foundations, and the experiences of foreign developed countries are also taken into account.